2012
DOI: 10.1186/1471-2458-12-552
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge exchange in the Pacific: The TROPIC (Translational Research into Obesity Prevention Policies for Communities) project

Abstract: BackgroundPolicies targeting obesogenic environments and behaviours are critical to counter rising obesity rates and lifestyle-related non-communicable diseases (NCDs). Policies are likely to be most effective and enduring when they are based on the best available evidence. Evidence-informed policy making is especially challenging in countries with limited resources. The Pacific TROPIC (Translational Research for Obesity Prevention in Communities) project aims to implement and evaluate a tailored knowledge-bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…The study builds on the Pacific Obesity Prevention In Communities (OPIC) project which took place from 2004–2009 [43] and the Translational Research on Obesity Prevention In Communities (TROPIC) project in 2010–2012 [21, 44]. Whilst the OPIC project targeted obesity amongst adolescents, a sub-study focused on food policy and identified potential policies and ranked them in terms of their likely cost-effectiveness and feasibility as measures to curb NCD growth [45].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study builds on the Pacific Obesity Prevention In Communities (OPIC) project which took place from 2004–2009 [43] and the Translational Research on Obesity Prevention In Communities (TROPIC) project in 2010–2012 [21, 44]. Whilst the OPIC project targeted obesity amongst adolescents, a sub-study focused on food policy and identified potential policies and ranked them in terms of their likely cost-effectiveness and feasibility as measures to curb NCD growth [45].…”
Section: Methodsmentioning
confidence: 99%
“…Whilst the OPIC project targeted obesity amongst adolescents, a sub-study focused on food policy and identified potential policies and ranked them in terms of their likely cost-effectiveness and feasibility as measures to curb NCD growth [45]. TROPIC targeted policies to tackle obesity and NCDs in Fiji and assessed how policy-making could be increased, and whether a knowledge brokering approach (focused on increasing access to and use of evidence) would be effective [44]. It developed the skills of key staff from four government ministries and two non-government organisations in evidence-use and policy brief development.…”
Section: Methodsmentioning
confidence: 99%
“…In order to gain the understanding and support of both government ministers and directors of non-government organizations (NGOs), concept papers detailing the benefits of TROPIC partnerships were tailored for each individual organization [52]. Ten government and non-government organizations were identified as potential participants.…”
Section: Methodsmentioning
confidence: 99%
“…Their roles were to advise the TROPIC team on policy processes and organizational culture throughout the knowledge brokering process [52]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation